Desain Pembelajaran Pendidikan Agama Islam Berbasis Kesadaran Lingkungan - Mundiro Lailatul Muawaroh (Universitas Islam Lamongan, 2019)
The low level of concern for the environment in society today is increasingly worrying. This reality has resulted in the emergence of several disasters caused by the lack of awareness about environmental sustainability. In this context, students' misunderstanding of the importance of protecting the school environment encourages the creation of a sense of indifference to create a comfortable school environment. Education can be used as a tool to foster love and awareness to manage the environment. This research uses qualitative research with descriptive analysis intended to reveal the phenomena that occur in the school environment related to environmental awareness. The data in this study were obtained through observation, interviews and documentation. Data analysis was performed by data reduction, data presentation and verification. Checking the validity of the data is done by conducting triangulation and member check. This study found that the learning process of PAI with environmental awareness can be done with a teaching design that emphasizes environmental awareness issues, both in the media, methods and learning materials. Environmental awareness-based PAI instructional design requires an educator to package learning, both in introductory, core and closing activities. The flow of this activity, then what makes students' understanding and attitudes related to environmental sustainability can develop well.